Pathogenic Significance of the DDX41 p.R525H Variant Revealed By Single-Cell RNA-Seq Analysis - Matsui, Hirotaka; Koizumi, Minori; Kudo, Rei; Nagamachi, Akiko; Ajiro, Masahiko; Harada, Hironori; Harada, Yuka; Shichino, Shigeyuki; Yoshimi, Akihide (Blood, 2024)
DDX41, encoding a DEAD-box type RNA helicase, is a crucial gene implicated in myeloid neoplasms with a germline predisposition. Typically, individuals harboring a germline pathogenic variant in one allele subsequently acquire a somatic variant, predominantly p.R525H, in the other allele prior to the development of myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). Germline DDX41 variants, primarily nonsense variants located at the gene's N-terminal, are thought to reduce DDX41 expression and function. However, the role of somatic variants within the helicase domain in disease progression remains unclear. We performed single-cell RNA sequencing (scRNA-seq) on CD34-positive hematopoietic stem/progenitor cells (HSPCs) from an MDS patient with DDX41 p.R339C germline and somatic p.R525H variants. In-house genomic panel sequencing revealed no co-occurring variants in TP53 or CUX1, suggesting MDS development in this case was driven by the DDX41 variants alone. scRNA-seq of CD34-positive HSPCs from bone marrow yielded a median of 5,657±1,627 genes and 34,333±19,786 reads per cell. In addition, single-cell genotyping in parallel with scRNA-seq enabled us to compare gene expression between cells with p.R525H and those with only the germline variant. Of 33,214 cells passing quality control, 7,207 harbored only the p.R339C germline variant, while 11,709 carried both p.R339C and p.R525H. Comparative scRNA-seq data from three healthy elderly subjects (GSE180298) provided controls. HSPCs with DDX41 variants were classified into 41 cell types using the BoneMarrowMap R package. Among 20 cell types with over 100 cells detected in both MDS and healthy controls, the MDS sample exhibited reduced hematopoietic stem cell (HSC) and increased granulocyte/monocyte progenitor (GMP)-Mono and GMP-Neut fractions. Gene regulatory network (GRN) analysis showed shifts in gene expression regulation by transcription factors such as KLF2, KLF4, and JUN/FOS, which are normally involved in HSC self-renewal, occurring also at the GMP level in MDS cells with DDX41 variants. This suggests enhanced self-renewal at the GMP level. GSEA analysis revealed no activation of NF-kappa B pathway, innate immune response, or Myc target genes, indicating a unique expression pattern distinct from typical MDS. We then compared cells with both the p.R339C germline variant and the p.R525H somatic variant to cells with only the p.R339C variant. Cells with the p.R525H variant showed further reductions in HSC and lympho-myeloid primed progenitor fractions and increased GMP ratios when compared with cells with p.R339C alone, despite no significant gene expression changes observed between cells with or without p.R525H in these cell types. Intriguingly, however, colony forming unit-erythroid (CFU-E) cells segregated into distinct clusters by genotype, with p.R525H cells specifically showing activated G2/M checkpoint and G2/M phase arrest. Previously, we demonstrated G2 arrest in hematopoietic cells with suppressed DDX41 expression or function due to increased replication stress and R-loop accumulation (Leukemia 2022, PMID: 36229594); similar effects are postulated in primary CFU-E cells with p.R525H. Although these changes were not evident in cells differentiating into myeloid lineages, some GMP cells displayed ectopic erythroid gene expression. GRN analysis indicated transcriptional induction of erythroid genes in these cells, suggesting that the p.R525H variant further alters the hematopoietic differentiation transcriptional network. In summary, our findings elucidate a mechanism by which the DDX41 p.R525H variant contributes to ineffective erythropoiesis and HSPC differentiation disruption, providing insights into the unique pathogenesis of the disease. Harada:Novartis Pharma Inc.: Research Funding. Shichino:ImmunoGeneTeqs, Inc.: Current Employment, Current holder of stock options in a privately-held company. Yoshimi:Chugai Pharmaceutical Co., Ltd.: Research Funding; Eisai Inc.: Research Funding.